Effect of maternal health education on physical activity and body mass index of overweight children - Miratul Haya; Maria Mexitalia; Ani Margawati (Paediatrica Indonesiana, 2016)
Background The percentage of overweight children in Bengkulu (16.4%) is higher than the national percentage (11.9%). High energy intake and low physical activity are two factors that cause overweight.Objective To assess the impact of maternal health education on changes in maternal behavior, as well as energy intake, physical activity level, and body mass index (BMI) z-scores in overweight children aged 3-6 years.Methods This study was a quasi-experiment with non-randomized, pre-post test control group, conducted in Bengkulu, Indonesia from January to April 2014. Subjects consisted of 48 mothers with overweight children, who were selected purposively and divided into 2 groups (treatment and control). Subjects’ parents kept records of their children’s food intake and daily activity. These records were used to measure energy intake and physical activity. Health education in the treatment group was conducted 6 times in 12 weeks, while the control group received health education only once at the beginning of the study.Results In the treatment group, the child physical activity level [0.04 (SD 0.01)] increased, while the % RDA for energy [-3.4 (SD 13.26)%] and BMI z-score [-0.57 (SD 0.26)] decreased. Significant differences were observed between the treatment and control groups in terms of maternal attitude, and children’s % RDA for energy, physical activity level, and BMI z-score after intervention (P <0.05).Conclusion Health education for mothers effects a positive change in maternal attitude, as well as increased physical activity level, decreased energy consumption relative to their need, and BMI z-score in overweight children.